Systematic review on digital transformation among teachers in public schools - Nor Asiah Razak; Roznim Mohamad Rasli; Suvarmani Subhan; Nor Aniza Ahmad; Shazia Malik (International Journal of Evaluation and Research in Education (IJERE), 2023)
Radical changes across almost all areas, including education, due to the COVID-19 outbreak. One of the rapid transformations is digital learning, also known as e-learning. Digital learning transformation has been taking place for more than a decade. However, little comprehensive analysis of digital transformation in teaching in public schools. To the best of the authors’ knowledge, no comprehensive analysis incorporates external and internal barriers and examines the prominent theories to study successful e-learning integration among teachers. The aim of this study was to provide a thematic and theoretical understanding of digital learning transformation among teachers in public schools. The data for the study was acquired from the Scopus databases. The study employed content and comparative analysis and advocated a grounded theory approach to inductively analyze and criticize the theme construction for answering two research questions. Based on a set of criteria to determine whether each derived study should be included or excluded, 42 articles were reviewed between 2010 and 2022. The analysis uncovered 10 themes of antecedents that were constructed as a framework based on the first-second-order barriers. Results also indicated that CHAT, TPACK, TAM, and UTAUT are the most prominent theories used to conduct digital transformation research. The findings offered significant implications for digital transformation and educational technology communities, especially for policymakers to strategize and reflect on the practice they implemented and improvised if necessary for future sustainable education and efficient teachers’ performance in teaching.